2016
DOI: 10.1007/s00192-016-2959-y
|View full text |Cite
|
Sign up to set email alerts
|

Perineal body stretch during labor does not predict perineal laceration, postpartum incontinence, or postpartum sexual function: a cohort study

Abstract: Introduction The perineum stretches naturally during obstetrical labor, but it is unknown if this stretch has a negative impact on pelvic floor outcomes after a vaginal birth (VB). We aimed to evaluate whether perineal stretch was associated with postpartum pelvic floor dysfunction. Materials and Methods This was a prospective cohort study of primiparous women who had a VB. Perineal body (PB) length was measured antepartum, during labor, and 6 months postpartum. We determined the maximum PB (PB Max) measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
(43 reference statements)
1
6
2
2
Order By: Relevance
“…However, the clinical significance of sexual dimorphism in perineal body muscle attachment is unclear. For example, stretching of the perineal body during pregnancy does not substantially impact defecatory, urinary or reproductive muscle function (Meriwether et al, ). Similarly, surgical dissection through the perineal body does not adversely affect the functions of superficial perineal muscles in either males or females (Kraima et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical significance of sexual dimorphism in perineal body muscle attachment is unclear. For example, stretching of the perineal body during pregnancy does not substantially impact defecatory, urinary or reproductive muscle function (Meriwether et al, ). Similarly, surgical dissection through the perineal body does not adversely affect the functions of superficial perineal muscles in either males or females (Kraima et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in ‘worst case’ simulations in which the air cuff was not deflated, the BD Odon Device did generate greater distention at the posterior fourchette compared with either forceps or Kiwi. Previous studies have not demonstrated a link between perineal distention in labour and anal sphincter injury . However, these findings suggest that incorrect use of the BD Odon Device, by not deflating the air cuff prior to crowning, may generate similar or higher rates of perineal tears compared with forceps and Kiwi ventouse, whereas correct use of the BD Odon Device produced similar perineal distention to the Kiwi.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have not demonstrated a link between perineal distention in labour and anal sphincter injury. 4 However, these findings suggest that incorrect use of the BD Odon Device, by not deflating the air cuff prior to crowning, may generate similar or higher rates of perineal tears compared with forceps and Kiwi ventouse, whereas correct use of the BD Odon Device produced similar perineal distention to the Kiwi. This finding highlights the importance of training accouchers to use the BD Odon Device correctly.…”
Section: Main Findingsmentioning
confidence: 88%
“…The Pelvic Organ Prolapse Quantification System (POP-Q) method has been used to establish the perineal skin length in term pregnancy, during second stage of labor, and postpartum [ 16 , 17 ]. The main result was that the perineal body measured with the POP-Q system increased during labor but the length during labor did not correlate with the degree of vaginal laceration.…”
Section: Discussionmentioning
confidence: 99%